Perishable Material Culture in Prehistory : Investigating the Missing Majority - Hurcombe, Linda M. (Taylor and Francis, 2014)
Cover -- Title -- Copyright -- Dedication -- CONTENTS -- List of tables, figures and plates -- Preface -- Acknowledgements -- 1 The holistic approach to material culture -- 2 The materiality of plants -- 3 The materiality of animals -- 4 Intimate relationships between plants, animals and people -- 5 Integrating craft and subsistence needs -- 6 Integrating organic and inorganic material culture -- 7 Conclusions -- Bibliography -- Index -- Plates.